Fluvial responses to late Holocene hydroclimate variability in the midcontinental United States. (1st February 2023) - Wright, Maxwell N.; Bird, Broxton W.; Gibson, Derek K.; Pollard, Harvie; Escobar, Jaime; Barr, Robert C.
Abstract: Long-term relationships between mean-state climatic conditions and flood frequencies in the midcontinental United States (US) are not well established because instrumental records of fluvial processes are limited to the current warm period (CWP; the last ca. 150 years) and continuous paleo-flood records are exceedingly rare. Here, we investigate climate-flood relationships in the midcontinental US by reconstructing flood frequencies at Half Moon Pond, a 1600-year-old oxbow lake on the lower White River, Indiana (watershed = ca, 29, 000 km 2 ). We used sediment accumulation rates and clastic fluxes constrained by high-resolution radiocarbon ( 14 C) dating. Frequent flooding, as indicated by high sedimentation rates and clastic fluxes to Half Moon Pond, occurred leading up to and during the Medieval Climate Anomaly (MCA; 950–1250 CE) when paleoclimate records suggest the predominance of ocean-atmosphere mean states resembling the negative phases of the Pacific Decadal Oscillation (-PDO-like) and Pacific North American Mode (-PNA-like). Reductions in sedimentation rates and clastic fluxes, indicating reduced flooding, subsequently occurred during the transition out of the MCA and into the Little Ice Age (LIA; 1250–1830 CE) as ocean-atmosphere conditions shifted to + PDO-like and +PNA-like mean states. Sedimentation rates and clastic fluxes increased again after ca. 1800 CE, indicating increased flooding during the CWP as ocean-atmosphere conditions returned to -PDO-like and -PNA-like mean states. The White River trends were notably antiphased with sedimentation-rate-based flood frequencies for the lower Ohio River (500, 000 km 2 watershed) prior to 1830 CE. This antiphased relationship is consistent with flooding in moderate to small watersheds in the Midwest being sensitive to the occurrence of rainstorm events, which were more frequent leading up to and during the MCA, and flooding in large watersheds being more sensitive to large spring melts associated with extensive snowpacks, which characterized the LIA. That both the White and Ohio rivers experienced their most frequent flooding during the CWP suggests deforestation and changing land use practices increased flooding on Midwestern watersheds across scales despite a current climatic mean state that in the past only resulted in increased flooding on moderate to small watersheds. Continued increased in midcontinental rainfall are therefore likely to enhance the occurrence of floods in Midwestern watersheds across different geographic scales. Highlights: Sediment accumulation rates and clastic flux records reveal Common Era flood frequencies for the White River, IN. Pacific North American mode-like (PNA-like) conditions were a primary driver of White River flooding. Positive (negative) PNA-like atmospheric circulation decreased (increased) White River flooding. White River flooding was anti-phased with the Ohio River. Watershed-scale responses to precipitation seasonality account for anti-phased White and Ohio river flood relationships.